Ad hoc networks : routing, QoS and optimization - Frikha, Mounir (ISTE ; Wiley, 2011)
This work presents ad hoc networks and their characteristics. It explains a new protocol of routing with QoS as well as its implementation in a network simulator and compares it with the existing protocols. The book discusses the principle of the load balancing, treats the approaches of optimization of energy, and proposes a new approach with an analytical model that gives a better performance.